Fiqh Analysis and Socio-Economic Factors in the Sale, Purchase, and Use of Pirated Goods - Mar’atus Sholiha; Rifqi (Lentera Peradaban: Journal on Islamic Studies, 2025)
This research aims to analyze the legal status (fiqh) of the sale, purchase, and use of pirated goods and to identify the determining factors that encourage the proliferation of this practice within society. Islam, as a comprehensive religion, regulates principles of property ownership justly and prohibits the acquisition of wealth through illicit means. The phenomenon of pirated goods, which are unauthorized replications of products without the copyright holder's permission, presents an ethical and juridical issue from an Islamic legal perspective. This study employs a qualitative method with a library research approach. Data analysis is conducted descriptively-analytically on primary sources such as the Qur'an and Hadith, as well as secondary sources including scholarly fatwas, classical fiqh books, academic journals, and intellectual property rights (IPR) legislation. The research findings indicate that the majority of scholars, including the fatwa of the Indonesian Ulema Council (MUI), prohibit the production, sale, and use of pirated goods. The basis for this prohibition stems from the fact that this practice contains elements of injustice (violation of rights), deception (tadlis), uncertainty (gharar), and usurpation of others' property rights (ghasab). Furthermore, this research identifies key contributing factors, including economic aspects (price disparity), cultural factors (consumerism and low legal awareness), technological advancements, and weak law enforcement. A holistic approach encompassing education, regulatory strengthening, and law enforcement is needed to effectively address this issue.